Improving the accuracy of the information retrieval evaluation process by considering unjudged document lists from the relevant judgment sets - Minnu Helen Joseph; SriDevi Ravana (Information Research: An International Electronic Journal)
Introduction. To improve user satisfaction and loyalty to the search engines, the performance of the retrieval systems has to be better in terms of the number of relevant documents retrieved. This can be evaluated through the information retrieval evaluation process. This study identifies two methodologies that help to recover and better rank relevant information resources based on a query, while at the same time suppressing the irrelevant one.